Development and functional analysis of an anticancer T‐cell medicine with immune checkpoint inhibitory ability. Issue 8 (7th April 2020) - Fujiwara, Kento; Shigematsu, Kazuki; Tachibana, Masashi; Okada, Naoki
Abstract: Adoptive cell therapy using patients' own T‐cells is expected to be an ideal cancer treatment strategy with excellent antitumor effects and low side effects. However, this therapy targeting solid tumors is unlikely to be effective because tumor tissues have an environment that suppresses T‐cell function. In particular, interaction between programmed death‐1 (PD‐1) and its ligand (PD‐L1) inhibits T‐cell activation by which T‐cells eliminate tumor cells. Here, we attempted to develop T‐cells that can exert potent antitumor activity even in tumor tissues by genetically modifying them to express the anti‐PD‐L1 membrane‐anchoring type single chain variable fragment (M‐scFv) that can inhibit PD‐L1/PD‐1 interaction. Anti‐PD‐L1 M‐scFv could be expressed on T‐cells while maintaining PD‐L1‐binding ability. Although T‐cell proliferation induced by CD3 stimulation was decreased depending on the PD‐L1 stimulation intensity, M‐scFv‐expressing T‐cells showed high proliferative activity even in the presence of PD‐L1 by avoiding the PD‐L1/PD‐1‐mediated suppression. Furthermore, M‐scFv‐expressing T‐cells showed higher cytotoxic activity against PD‐L1 high tumor cells than that of mock T‐cells. The effect of PD‐L1/PD‐1 blockade was more pronounced when the therapeutic target was low‐antigenic tumor cells with low major histocompatibility complex expression, presenting only the shared antigen. These results indicated that anti‐PD‐L1 M‐scFv expression was functional in avoiding T‐cell dysfunction by PD‐L1/PD‐1 interaction. Our concept of anti‐PD‐L1 M‐scFv‐expressing T‐cells is thus expected to improve the efficacy of T‐cell therapy and contribute to simplify the treatment system and reduce treatment costs compared with the combination therapy of T‐cells and antibodies.